أثر تطبيق سياسات التسويق الداخلي على رضا العاملين في البنوك الجزائرية، دراسة حالة القرض الشعبي الجزائري Cpa - عمورات أعراب (My University, 2017)
يهدف هذا البحث إلى معرفة مدى تطبيق سياسات التسويق الداخلي (التوظيف، التدريب، التحفيز، والاتصال الداخلي) في بنك القرض الشعبي الجزائري CPA وأثرها على رضا العاملين لديها. وتوصل البحث بأن البنك محل الدراسة يطبق سياسات التسويق الداخلي ماعدا نظام الحوافز حيث يعتبره العاملون نظام غير فعال وغير عادل. وخلص أيضا إلى وجود علاقة بين هذه السياسات ومستوى الرضا الوظيفي. This study aims to identify the extent of implementation of the CPA bank for internal marketing policies (recruitment, training, incentive, internal communication) and its impact on the satisfaction of employees. The results of study, find that the bank under study, applies internal marketing policies, except for incentive system, which is considered by employees as inefficient and unfair. Moreover, the study find that there is relationship between those policies and the level of job satisfaction.
يهدف هذا البحث إلى معرفة مدى تطبيق سياسات التسويق الداخلي (التوظيف، التدريب، التحفيز، والاتصال الداخلي) في بنك القرض الشعبي الجزائري CPA وأثرها على رضا العاملين لديها. وتوصل البحث بأن البنك محل الدراسة يطبق سياسات التسويق الداخلي ماعدا نظام الحوافز حيث يعتبره العاملون نظام غير فعال وغير عادل. وخلص أيضا إلى وجود علاقة بين هذه السياسات ومستوى الرضا الوظيفي. This study aims to identify the extent of implementation of the CPA bank for internal marketing policies (recruitment, training, incentive, internal communication) and its impact on the satisfaction of employees. The results of study, find that the bank under study, applies internal marketing policies, except for incentive system, which is considered by employees as inefficient and unfair. Moreover, the study find that there is relationship between those policies and the level of job satisfaction
Keywords: التسويق الداخلي، الرضا الوظيفي، التوظيف، التدريب، التحفيز، الاتصال الداخلي، القرض الشعبي الجزائري CPA